The effect of lone motherhood on the smoking behaviour of young adults - Marco Francesconi; Stephen P. Jenkins; Thomas Siedler (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We provide evidence that living with an unmarried mother during childhood raises smoking propensities for young adults in Germany.
Keywords: 330